Unveiling the engines of fast radio bursts, superluminous supernovae, and gamma-ray bursts. Issue 2 (5th September 2018) - Margalit, Ben; Metzger, Brian D; Berger, Edo; Nicholl, Matt; Eftekhari, Tarraneh; Margutti, Raffaella
ABSTRACT: Young, rapidly spinning magnetars are invoked as central engines behind a diverse set of transient astrophysical phenomena, including gamma-ray bursts, superluminous supernovae (SLSNe), fast radio bursts (FRBs), and binary neutron star (NS) mergers. However, a barrier to direct confirmation of the magnetar hypothesis is the challenge of directly observing non-thermal emission from the central engine at early times due to the dense surrounding ejecta. We present CLOUDY calculations of the temperature and ionization structure of expanding supernova or merger ejecta due to photoionization by a magnetar engine, studying the escape of X-rays and radio waves (absorbed by neutral/ionized gas, respectively), and the evolution of the local dispersion measure due to photoionization. We find that ionization break-out does not occur if the engine's ionizing luminosity decays rapidly, and that X-rays typically escape the oxygen-rich ejecta of SLSNe only after ${\sim } 3-30 \, {\rm yr}$, consistent with current non-detections. We apply these results to constrain engine-driven models for the binary NS merger GW170817 and the luminous transient ASASSN-15lh. In terms of radio transparency and dispersion measure constraints, the repeating FRB 121102 is consistent with originating from a young, ${\gtrsim } 30-100 \, {\rm yr}$, magnetar similar to those inferred to power SLSNe. We further show that its high rotation measure can be produced within the same nebula proposed to power the quiescent radio source observed co-located with FRB 121102. Our results strengthen previous work suggesting that at least some FRBs may be produced by young magnetars, and motivate further study of engine-powered transients.